In vivo pharmacokinetic and ADMET profiles of synthetic antimicrobial peptides (AMPs) - Mohd Noordin, Muhammad Akram; Najm, Ahmed Abdulkareem; Dyari, Herryawan Ryadi Eziwar; Law, Douglas; Syed Alwi, Sharifah Sakinah; Mat Lazim, Azwan; Cheah, Yew Hoong; Tee, Thiam Tsui; Fazry, Shazrul (Bentham Science Publishers, 2025)
The broad-spectrum action and capacity to target drug-resistant infections make synthetic Antimicrobial Peptides (AMPs) popular therapeutic agents. Indeed, the effective use of these peptides in clinical application relies on a thorough understanding of their Pharmacokinetic (PK) and ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) characteristics. Despite growing research on synthetic AMPs, there is a notable gap in the literature specifically addressing their ADMET profiles. Previous reviews have not extensively covered this area, providing a vital opportunity to study synthetic AMPs' pharmacokinetics and safety, which are crucial for their therapeutic development. This review covered research studies that focused on PK and ADMET of synthetic antimicrobial peptides from several databases, including Google Scholar, SCOPUS, PubMed, and Science Direct, within the years 2020 to 2024, and 12 related research papers have been found. AMPs display a wide range of PK behaviors, including rapid renal clearance, liver-centric distribution, broad distribution with low toxicity, high kidney retention, and gradual absorption with dose-dependent toxicity. Overall, the ADMET profiles of AMPs are crucial in assessing their therapeutic potential, and continuous study is necessary to enhance their practical feasibility. An in-depth investigation of the in vivo ADMET and pharmacokinetic profiles of synthetic AMPs is presented in this review to address the current gap in the research. The findings of this study provide important insights for developing synthetic AMPs as effective antimicrobial drugs.